2019
DOI: 10.33885/sf.2019.49.1256
|View full text |Cite
|
Sign up to set email alerts
|

Using mushroom-forming fungi in preventing and reducing mycotoxins in cereal products

Abstract: Background: Biological control for cereal diseases caused by mycotoxigenic fungi is part of the alternative methods to be developed to secure food and feed production, recognizing the negative effects these fungi have on crop yield and their potential production of mycotoxins. Objective: Update recent knowledge about the potential of mushroom-forming fungi as biological control agents of mycotoxigenic fungi species, acting as antagonists on crop debris, as source of active extracts with antifungal and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 130 publications
(153 reference statements)
0
4
0
Order By: Relevance
“…A limit to the future development of such extracts as bio-control products could be the production cost and competition with food uses of mushrooms. However, because of their degrading capacities, it is possible to cultivate these mushrooms intended for the production of extracts on contaminated substrates and thus recycle them [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A limit to the future development of such extracts as bio-control products could be the production cost and competition with food uses of mushrooms. However, because of their degrading capacities, it is possible to cultivate these mushrooms intended for the production of extracts on contaminated substrates and thus recycle them [35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ethanolic extracts of Hydnum repandum , a mycorrhizal species commonly known as the sweet tooth or hedgehog mushroom and broadly distributed in Europe and Asia, had strong antifungal effects on various Fusarium species, including F. verticillioides [ 41 ]. Nonetheless, to date, there are no previous studies that showed inhibition of F. verticillioides by extracts from A. subrufescens , L. edodes , or P. ostreatus [ 35 ]. The concentration of CEs used in this study was selected based on the previous report of Stojkovic et al [ 39 ], who identified antifungal activity at a concentration around 2 mg mL −1 of a methanolic extract from A. subrufescens (or A. brasiliensis ) fruiting bodies, and after a preliminary concentration-response analysis on both mycelial growth and mycotoxin production, using whole fruiting bodies of A. subrufescens .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Edible mushrooms are macro fungus with a specific fruiting body, which can be either a Basidiomycete or an Ascomycete , aerial or underground, and large enough to be seen with naked eye and to be collected by hand [ 189 ]. Mushroom oyster or white-rot fungus ( Pleurotus ostreatus ) is one of the most well-known edible mushrooms due to its economic (edible), ecological (bioremediation agents), and medicinal value (antioxidant activity and bio-compounds source) [ 190 , 191 ].…”
Section: Progress In Detoxificationmentioning
confidence: 99%